Comparative Effects of Ohmic, Induction Cooker, and Electric Stove Heating on Soymilk Trypsin Inhibitor Inactivation. Issue 3 (10th February 2015) - Lu, Lu; Zhao, Luping; Zhang, Caimeng; Kong, Xiangzhen; Hua, Yufei; Chen, Yeming
Abstract During thermal treatment of soymilk, a rapid incorporation of Kunitz trypsin inhibitor (KTI) into protein aggregates by covalent (disulfide bond, SS) and/or noncovalent interactions with other proteins is responsible for its fast inactivation of trypsin inhibitor activity (TIA). In contrast, the slow cleavage of a single Bowman–Birk inhibitor (BBI) peptide bond is responsible for its slow inactivation of TIA and chymotrypsin inhibitor activity (CIA). In this study, the effects of Ohmic heating (220 V, 50 Hz) on soymilk TIA and CIA inactivation were examined and compared to induction cooker and electric stove heating with similar thermal histories. It was found that: (1) TIA and CIA inactivation was slower from 0 to 3 min, and faster after 3 min as compared to induction cooker and electric stove. (2) The thiol (SH) loss rate was slower from 0 to 3 min, and similar to induction cooker and electric stove after 3 min. (3) Ohmic heating slightly increased protein aggregate formation. (4) In addition to the cleavage of one BBI peptide bond, an additional reaction might occur to enhance BBI inactivation. (5) Ohmic heating was more energy‐efficient for TIA and CIA inactivation. (6) TIA and CIA inactivation was accelerated with increasing electric voltage (110, 165, and 220 V) of Ohmic heating. It is likely that the enhanced inactivation of TIA by Ohmic heating is due to its combined electrochemical and thermal effects.